The effectiveness of psychological interventions in improving quality of life and satisfaction with treatment in the elderly with mental disorders and multimorbidity - Kalugin, Igor; Khaustova, Olena; Osukhovska, Olena (Psychosomatic Medicine and General Practice, 2017)
Background. The state of polymorbidity is common for the elderly patients. Older adults with mental illness often suffer from several somatic diseases. The mutual influence of these diseases changes the classical clinical picture, the nature of their course, increases the number of complications and their severity, worsens the quality of life and prognosis. As a result, the healing process is complicated; compliance and patient’s satisfaction decreases. Individuals with polymorbidity are prone to non-compliance with medical recommendations, self-treatment and passive relationships in the medical process. Aim. To determine the impact of psychotherapy on the life quality and medical care satisfaction in elderly patients with mental disorders and polymorbidity. Methods. In a randomized controlled trial, participated 325 elderly patients with mental disorders and polymorbidity. The control group (n=87) received standard medical care; intervention group (n=238) in addition to standard care was involved in a psychotherapeutic program. It consisted of psycho-education, compliance therapy, and self-medication prevention training. Patients were assessed with SF-36, PSQ, MMAS, and MMSE scale. The statistical processing of the results was carried out using the SPSS program. Results. After the treatment was noted significant improvement in patients’ satisfaction with treatment (PSQ score), regardless of its volume (8.32 points; p<0.001). Changes in PSQ in the intervention group were significantly more pronounced compared to control group relative to the comparator group (3.63 points; p<0.001). A more significant improvement in the quality of life due to inpatient treatment was demonstrated by younger patients (r= -0.149; p=0.007), in those with a lower deficit in cognitive functioning (r = 0.282; p<0.001). Increased satisfaction with the medical care was directly correlated with number of drugs in the constant treatment scheme (r=0,121; p=0.029) and inversely - with additional periodic dosing (r = -0.134; p =0.015). Conclusion. The study showed that psychological interventions are effective in improvement of the quality of life and patient’s satisfaction by treatment.